Dynamic thermal performance of inclined double-skin roof: Modeling and experimental investigation. (15th August 2017) - Zingre, Kishor T.; Yang, En-Hua; Wan, Man Pun
Abstract: A novel double-skin roof heat transfer (DSRHT) model is proposed to capture the dynamic thermal behavior of open-ended double-skin roof (DSR). The proposed model is validated against field measurements performed in a 13-storey-tall, naturally-ventilated residential building in Singapore. DSR exhibits dynamic thermal behavior of having an equivalent thermal resistance (or R-value = 1/U-value) 4–5 times higher during daytime than that during night-time, mainly due to the presence of an open-ended air-gap. Such dynamic behavior makes DSR more effective to prevent heat gain into the building during daytime and allow heat loss during night-time, compared to a reference flat insulated roof having a fixed R-value, in hot climate. The DSRHT model is further used to investigate the effect of roof inclination angle and climatic conditions on heat transfer through the roof. With increase in inclination angle (from 0° to 60°), annual heat curbing performance of an insulated roof enhances by 30% (as R - value increases from 4.2 to 6.0 m 2 -K/W), while that of a comparable DSR enhances marginally by 6% (as R - value increases from 5.2 to 5.6 m 2 -K/W). Comparison of annual heat gain trends of a DSR against an insulated roof for five different climate conditions showed that the DSR performance in curbing annual heat gain increases with annual-averaged solar-air temperature. Highlights: A novel inclined double-skin roof heat transfer (DSRHT) model is proposed. DSRHT model is concise and easy-to-use for dynamic thermal analysis. DSRHT model is validated against field measurements on sunny and cloudy days. DSRHT model is further used for parametric analysis in various climates. Double-skin roof performance compared against insulated roof in various climates.